(untitled) (CIPEEX, 2025)
Mitochondria are essential organelles for cellular metabolism, playing a key role in ATP production through oxidative phosphorylation. This study aims to analyze the role of mitochondria in metabolic regulation and their association with metabolic diseases. The methodology involved a literature review of scientific articles published between 2022 and 2025, focusing on mitochondrial bioenergetics, oxidative stress, and cellular signaling. The results indicate that mitochondrial dysfunction leads to excessive production of reactive oxygen species (ROS), compromising energy homeostasis and contributing to the development of diseases such as type 2 diabetes, obesity, and neurodegenerative disorders. It is concluded that preserving mitochondrial integrity is crucial for metabolic balance, and that therapeutic strategies aimed at improving mitochondrial function represent a promising approach for the treatment of chronic diseases.